2021
DOI: 10.1186/s12872-021-02022-5
|View full text |Cite
|
Sign up to set email alerts
|

Postural changes in blood pressure among patients with diabetes attending a referral hospital in southwestern Uganda: a cross-sectional study

Abstract: BackgroundOrthostatic hypotension (OH) and orthostatic hypertension (OHT) are often unrecognized in clinical care for diabetic individuals, yet they are associated with increased risk for adverse cardiovascular outcomes. We aimed to determine the prevalence of the abnormal orthostatic blood pressure (BP) responses, and associated factors among diabetic individuals in ambulatory care for diabetes in southwestern Uganda.MethodsWe conducted a cross-sectional study among diabetic individuals aged 18–65 years at Mb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 20 Cardiovascular diseases research area. We realized 13 publications from the MURTI trainees in this area: (i) PMC5766276 21 (ii) https://doi.org/10.29392/001c.19464 ; 22 (iii) PMC7470164; 23 (iv) PMC7218768; 24 (v) PMC8077796; 25 (vi) https://doi.org/10.1007/s13410-021-00944-6 ; 26 (vii) https://doi.org/10.11604/pamj.2021.39.142.28620 (viii) PMC7367467; 28 (ix) PMC6877961; 29 (x) PMC7396089; 30 (xi) PMC7004860; 31 (xii) PMC6641537; 32 (xiii) PMC7592727. 33 Neurological disorders and stroke research area.…”
Section: Resultsmentioning
confidence: 99%
“… 20 Cardiovascular diseases research area. We realized 13 publications from the MURTI trainees in this area: (i) PMC5766276 21 (ii) https://doi.org/10.29392/001c.19464 ; 22 (iii) PMC7470164; 23 (iv) PMC7218768; 24 (v) PMC8077796; 25 (vi) https://doi.org/10.1007/s13410-021-00944-6 ; 26 (vii) https://doi.org/10.11604/pamj.2021.39.142.28620 (viii) PMC7367467; 28 (ix) PMC6877961; 29 (x) PMC7396089; 30 (xi) PMC7004860; 31 (xii) PMC6641537; 32 (xiii) PMC7592727. 33 Neurological disorders and stroke research area.…”
Section: Resultsmentioning
confidence: 99%
“…21 Migisha and coworkers cross-sectional investigation of younger individuals in Uganda (mean age, 50 years) with BP measurements taken in supine position and within 3 min of standing, reported that 12.7% of diabetic individuals showed evidence of diastolic OHT. 31 The current hypertension guidelines do not provide recommendations for the management of OHT 32 of coronary disease and post-myocardial infarction. 23 Beta-blockers prescribed as an add-on therapy to RAAS blockers + dCCBs combination, have been shown to improve survival and decrease the risk of recurrent myocardial infarction 35 independent of providing additive BP lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wijkman and coworkers, using a similar definition of diastolic OHT in their cohort of patients with type 2 diabetes in the Cardiovascular Risk factors in Patients with Diabetes—a Prospective study in Primary care (CARDIPP study) in Sweden, reported that 18.7% (mean age, 60 years) showed diastolic OHT 21 . Migisha and coworkers cross‐sectional investigation of younger individuals in Uganda (mean age, 50 years) with BP measurements taken in supine position and within 3 min of standing, reported that 12.7% of diabetic individuals showed evidence of diastolic OHT 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation